[Cavernous malformations] - Ahlhelm, F; Hagen, T; Schulte-Altedorneburg, G; Grunwald, I; Reith, W; Roth, C (2007)
Cavernomas of the CNS may involve brain parenchyma as well as the spinal cord and belong to those cerebrovascular malformations that have no arteriovenous shunt and thus are generally angiographically occult. Contrary to computed tomography (CT), which is generally suited to reveal calcifications or acute bleeding, magnetic resonance imaging (MRI) enables detection of even small cavernomas. A frequently associated venous anomaly is helpful for correct diagnosis.